Unfixable Forms : Disability, Performance, and the Early Modern English Theater - Schaap Williams, Katherine, 1983- (Book collections on Project MUSE., 2021)
"This book analyzes physical disability in sixteenth-century and seventeenth-century English plays by Shakespeare, Dekker, Jonson, Middleton, and others to show how disability is a product of and catalyst for theatrical performance in the early modern theater"--